2013
DOI: 10.1186/1471-2393-13-177
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal mortality following assisted reproductive technology treatment in Australia and New Zealand, a public health approach for international reporting of perinatal mortality

Abstract: BackgroundThere is a need to have uniformed reporting of perinatal mortality for births following assisted reproductive technology (ART) treatment to enable international comparison and benchmarking of ART practice.MethodsThe Australian and New Zealand Assisted Reproduction Database was used in this study. Births of ≥ 20 weeks gestation and/or ≥ 400 grams of birth weight following embryos transfer cycles in Australia and New Zealand during the period 2004 to 2008 were included. Differences in the mortality rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The retrospective nature of this study is another limitation as it questions the causal relationship, in limiting the analysis to four variants, and in the lack of testing all participants for chromosomal abnormalities due to financial considerations. While the chromosomal abnormalities are an important cause of miscarriage, with karyotypic abnormalities seen 2%–8% of couples with RPL in the first trimester of pregnancy, 44,45 RPL could happen even if the embryo has a normal genetic profile 46 . These limitations require further investigations in order to fully explain the role of FOXP3 in idiopathic RPL and to support or exclude the association of FOXP3 variants with altered FOXP3 expression and the pathophysiology of idiopathic RPL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The retrospective nature of this study is another limitation as it questions the causal relationship, in limiting the analysis to four variants, and in the lack of testing all participants for chromosomal abnormalities due to financial considerations. While the chromosomal abnormalities are an important cause of miscarriage, with karyotypic abnormalities seen 2%–8% of couples with RPL in the first trimester of pregnancy, 44,45 RPL could happen even if the embryo has a normal genetic profile 46 . These limitations require further investigations in order to fully explain the role of FOXP3 in idiopathic RPL and to support or exclude the association of FOXP3 variants with altered FOXP3 expression and the pathophysiology of idiopathic RPL.…”
Section: Discussionmentioning
confidence: 99%
“…of couples with RPL in the first trimester of pregnancy, 44,45 RPL could happen even if the embryo has a normal genetic profile. 46 These limitations require further investigations in order to fully explain the role of FOXP3 in idiopathic RPL and to support or exclude the association of FOXP3 variants with altered FOXP3 expression and the pathophysiology of idiopathic RPL.…”
Section: As Foxp3 Controls Treg Cells Development and Function And As...mentioning
confidence: 99%
“…However, singletons conceived by ART have also been demonstrated to have increased rates of prematurity, low birth weight and perinatal mortality. 75 Recently, two commonly used culture media were observed to be associated with a 200 g difference in birth weighta similar difference to that seen among women that smoke throughout pregnancy compared with non-smoking women. 76 Numerous studies in animal model systems have shown that ART can have important and lasting consequences on health in later life.…”
Section: Room 5: Assisted Reproductionmentioning
confidence: 83%
“…For example, in many countries the policy of transferring two or more embryos has now been restricted 73 because of unacceptably high multiple pregnancy rates, 74 with accompanying high perinatal morbidity and mortality. However, singletons conceived by ART have also been demonstrated to have increased rates of prematurity, low birth weight and perinatal mortality 75 . Recently, two commonly used culture media were observed to be associated with a 200 g difference in birth weight – a similar difference to that seen among women that smoke throughout pregnancy compared with non-smoking women 76 …”
Section: Room 5: Assisted Reproductionmentioning
confidence: 99%
“…The absence of antenatal care is a crucial factor that determines pregnancy outcomes. Clearly, neonatal deaths are higher among those mothers with poor antenatal attendance (1.6% versus 0.4%, with a p-value of 0.0001 and OR of 3.4) [12,13]. Kim et al demonstrated that even within both the United States and other developed countries, the evidence in two-thirds of studies suggests that low income, unemployment, poor neighborhood status, limited access to the health care system, and little or no antenatal care all play a role in infant mortality and neonatal outcome [14].…”
Section: Discussionmentioning
confidence: 97%